Panic buying research: A systematic literature review and future research agenda - Soniya Billore; Tatiana Anisimova (International Journal of Consumer Studies, 2021)
Panic buying has re-emerged as a 'new' normal consumer behavior and has become a coping mechanism for real and perceived dangers associated with COVID-19. Despite the need for a better understanding of the panic buying phenomenon, there has been a lack of scholarly research on this topic. This study seeks to fill this gap. In this article, we systematically review extant studies in panic buying from the last two decades. We analyze and categorize them according to Callahan's 4W (2014) review structure and Paul and Rosado-Serrano's (2019) TCCM framework. We found that the existing publications in panic buying are fragmented across multiple disciplines. Due to the nature of the panic-induced behavior, most of them have been written as a reaction to the pandemic crisis. We contribute to marketing research by providing theoretical, contextual, and methodological insights into the field of panic buying. Furthermore, we develop a research agenda related to retailer and consumer perspectives. Additionally, we identify research issues related to policymaking and governance, as well as broader societal impacts that need to be addressed in the future.
Keywords: 330; consumer perspective; COVID-19; panic buying; future research agenda; retailer perspective; systematic literature review